2018
DOI: 10.1126/science.aao6135
|View full text |Cite
|
Sign up to set email alerts
|

A pathway for mitotic chromosome formation

Abstract: Mitotic chromosomes fold as compact arrays of chromatin loops. To identify the pathway of mitotic chromosome formation, we combined imaging and Hi-C of synchronous DT40 cell cultures with polymer simulations. We show that in prophase, the interphase organization is rapidly lost in a condensin-dependent manner and arrays of consecutive 60 kb loops are formed. During prometaphase ~80 kb inner loops are nested within ~400 kb outer loops. The loop array acquires a helical arrangement with consecutive loops emanati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

108
903
3
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 670 publications
(1,018 citation statements)
references
References 100 publications
108
903
3
4
Order By: Relevance
“…A conceivable mechanism for lengthwise compaction is progressive “extrusion” of chromatin loops by condensins (Marko, 2011, Alipour and Marko, 2012, Marko, 2009, Nasmyth, 2001, Goloborodko et al, 2016a, Goloborodko et al, 2016b, Gibcus et al, 2018, Ganji et al, 2018). In such a model, condensin II would act to push chromatin to the exterior of the chromosome, perhaps in concert with condensin-associated factors such as the chromokinesin KIF4, (Samejima et al, 2012), with crowding of chromatin loops providing a thermodynamic drive for topo II to remove interlocks between different chromatids and chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…A conceivable mechanism for lengthwise compaction is progressive “extrusion” of chromatin loops by condensins (Marko, 2011, Alipour and Marko, 2012, Marko, 2009, Nasmyth, 2001, Goloborodko et al, 2016a, Goloborodko et al, 2016b, Gibcus et al, 2018, Ganji et al, 2018). In such a model, condensin II would act to push chromatin to the exterior of the chromosome, perhaps in concert with condensin-associated factors such as the chromokinesin KIF4, (Samejima et al, 2012), with crowding of chromatin loops providing a thermodynamic drive for topo II to remove interlocks between different chromatids and chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Hi-C results obtained with mitotic cells were modeled using polymer-based simulations of chromatin structure, and it was proposed that chromatin in mitotic chromosomes is folded as a compact array of many loops having different sizes during mitosis (Gibcus et al, 2018). For chromatids with a radius of~0.36 lm (Gibcus et al, 2018), this linear density corresponds to~150 Mb/lm 3 . For chromatids with a radius of~0.36 lm (Gibcus et al, 2018), this linear density corresponds to~150 Mb/lm 3 .…”
Section: Of 12mentioning
confidence: 99%
“…In vitro experiments showed that the compaction degree of the chromatin filament is extremely dependent on ionic conditions (Daban, 2011;Collepardo-Guevara & Schlick, 2012;Grigoryev & Woodcock, 2012;Luger et al, 2012;Rippe, 2012;Boulé et al, 2015). The analysis of chromosomes in different condensation stages indicated a hierarchical folding of fibers having diameters from 30 to 250 nm (Kireeva et al, 2004), and studies of chromosome conformation capture suggested that mitotic chromosomes are formed by a compact array of chromatin loops (Gibcus et al, 2018). Several structural models have been proposed for the organization of chromatin in metaphase chromosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it fails to form a cyclic trajectory. [18] In brief, CDD captures contact probability profile, PCC and Ins record higher-order structural properties, and MCM suggests macro information of genomic architecture. PCC representing loop signal possesses abundant cell-cycle information to distinguish cells at different phases, but there are many outliers which are significantly deviated from original phases (Figure 2A,B).…”
Section: The Reconstructed Trajectories Of Four Individual Feature Sementioning
confidence: 99%